Pengaruh Word of Mouth dan Product Innovation Terhadap Minat Beli Konsumen Tetra Coffee Palembang: Pengaruh Word of Mouth dan Product Innovation Terhadap Minat Beli Konsumen Tetra Coffee Palembang - Liananda, Inka; Siti Komariah Hildayanti; Mohammad Kurniawan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
This study aims to determine the influence of word of mouth and product innovation on the buying interest of Tetra Coffee Palembang consumers. This research method is a descriptive method with a quantitative research approach. The sampling technique in this study uses the probability sampling method with a simple random sampling approach. Determination of the number of samples using the Lemeshow formula obtained the minimum number of samples needed in this study was 96 respondents. Data analysis using data quality tests, classical assumption tests, and multiple linear regression analysis. The result of this study is that word of mouth (X1) has a positive and significant effect on consumer buying interest (Y) at Tetra Coffee Palembang. Product innovation (X2) has a positive and significant effect on consumer buying interest (Y) at Tetra Coffee Palembang. Word of mouth (X1) and product innovation (X2) have a positive and significant effect on consumer buying interest (Y) at Tetra Coffee Palembang. Based on the results of the variables X1 and X2 together there is a Y in RSquare of 0.870, this means that the influence of the variables word of mouth (X1) and product innovation (X2) together on and buying interest (Y) is 87%. The remaining 13% was influenced by variables other than the variables studied.